National-scale Level of Service Determining of Urban Streets Using Online Traffic Data - Boonsiripant, Saroch; Malaikrisanachalee, Suphawut; Supavetch, Sorawit; Preeda, Akachai; Phamornmongkhonchai, Monthira (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Level of service (LOS) is one of the widely used highway performance measurements. Road authorities can develop road improvement programs for roadways with poor levels of service, such as upgrading the road infrastructure or optimizing traffic signal timings. However, traditional methods of determining the level of service at a regional or national scale could be costly and time-consuming, and they cannot determine the priority of road subsections that require improvement. To implement the challenges of high cost and time-consuming data collection, using online traffic data such as Google Maps can provide real-time and comprehensive traffic information at a relatively low cost and without the effort of collecting large amounts of field data. In this paper, we propose a methodology to determine the level of service of the urban streets of road network at a national scale using online traffic data, i.e., travel speed and free-flow speed with traffic condition from Google Maps. The methodology includes road subsections, data input preparation, and level of service determination. The analysis is divided into three time periods (i.e., AM, MD, and PM) for both weekdays and weekends. The analysis results yielded a level of service from A to F for urban street links in Thailand. The challenges and limitations of this proposed methodology were also discussed in the paper. Road authorities can use the proposed methodology as a screening tool to identify links with the level of service issues at a regional/national scale to improve the roadway network.